A simple and software-independent protocol for the measurement of post-cranial bones in anthropological contexts using thin slab maximum intensity projection. (March 2020) - Spake, Laure; Meyers, Julia; Blau, Soren; Cardoso, Hugo F.V.; Lottering, Nicolene
Highlights: This paper introduces a new measurement protocol for post-cranial bones. Tests show the protocol is both highly repeatable and accurate. Protocol can be implemented in most DICOM viewers with measurement capability. Protocol does not require exportation of an isosurface to other software. Method is of interest to both forensic radiologists and forensic anthropologists. Abstract: Objective: This paper introduces a new protocol for the measurement of post-cranial bones in computed tomography using slab maximum intensity projection. Materials and Methods: The steps of the protocol are described and illustrated. Repeatability and accuracy are established through inter and intra observer testing evaluated using TEM, rTEM, and R. Results: The protocol performed well in both repeatability and accuracy testing. Conclusion: The protocol yields highly repeatable and accurate measurements.